Synthesis by UV-curing and characterisation of polyurethane acrylate-lithium salts-based polymer electrolytes in lithium batteries - KILIÇ, HASAN (WALTER DE GRUYTER GMBH, 2014)
UV-cured caprolactone-based polyurethane acrylate (PUA) polymer blend electrolytes were prepared and characterised. To develop polymer electrolytes suited to ambient temperature, an ionically-conductive and reliable polymer electrolyte based on urethane acrylate resins synthesised from a fluorine-containing di-functional oligomer 6F ethoxylated diacrylate, a di-functional reactive diluent 1,6-hexanediol diacrylate for adjusting the viscosity, and a radical photo-initiator doped with a mixture of lithium salts were used. Free-standing flexible electrolyte films were prepared by UV-curing via free-radical photopolymerisation. The performance of the lithium polymer cell system (Li/PE(F4)/LiCoO2) was determined by electrochemical impedance spectroscopy, cyclic voltammetry, a galvanostatic recurrent differential pulse, chronocoulometry and chronoamperometry. The electrolyte with optimal amounts of fluorine-containing oligomer and optimal salt mixture content exhibited enhanced conductivity, showing a conductivity of 1.00 x 10(-4) S cm(-1) at ambient temperature. The specific capacity, specific energy and specific power of a Li/PE(F4)/LiCoO2 cell were also determined.
Keywords: polymer blends; conducting polymers; membranes; polyurethanes; IONIC-CONDUCTIVITY; MECHANICAL-PROPERTIES; COMPLEXES; METHACRYLATE); TECHNOLOGY; COPOLYMERS; COATINGS; FILMS